2021
DOI: 10.25078/klgw.v11i2.2647
|View full text |Cite
|
Sign up to set email alerts
|

Afiksasi Bahasa Bali Suatu Kajian Morfofonemik

Abstract: <p><span lang="EN-IN">This study aims to describe the morphophonemic process that occurs as a result of the affixing process. The theory used in this research is the theory of Generative Morphology and Phonology (Schane, 1992). The results of this study indicate; (1) there is a change in sound that produces a new sound due to the meeting of two different morphemes, such as: nasal /ŋ/ becomes a homogeneous sound with preexisting obstruent sounds, such as [p, b, d, t, c , j, s, k, g] and changes in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…If referring to the affixation process that occurs in the Tajen lexicon, it can be analysed that all affixes added to the basic form are derivational affixes because the attached affixes have the ability to change the word class from the basic form to the derived form. The prefix ng-which was found n this study in line with the result of previous research undertaken by Mahardika et al which also found that the prefix ng-was categorized as the derivational affix (Mahardika et al, 2021). Regarding reduplication, there are only two data found that can be classified into reduplication.…”
supporting
confidence: 91%
“…If referring to the affixation process that occurs in the Tajen lexicon, it can be analysed that all affixes added to the basic form are derivational affixes because the attached affixes have the ability to change the word class from the basic form to the derived form. The prefix ng-which was found n this study in line with the result of previous research undertaken by Mahardika et al which also found that the prefix ng-was categorized as the derivational affix (Mahardika et al, 2021). Regarding reduplication, there are only two data found that can be classified into reduplication.…”
supporting
confidence: 91%